Investigation of the glass transition temperature and damping of an acrylic/epoxy bonding tape using the peak damping method. Issue 13 (10th November 2018) - Kadioglu, Ferhat; Adams, Robert D.
ABSTRACT: The dynamic properties of a structural tape used for adhesive bonding applications have been measured at different temperatures to determine its glass transition temperature and damping properties. For this purpose, free layer beams consisting of a base layer steel and the tape layer were vibrated using a resonant beam technique with free-free end conditions. To measure the dynamic values (elastic modulus and loss factor) of the tape, the necessary equations were derived and the frequency dependence of the beams was investigated from –55°C to +60°C. Three beams with different layers were tested. Results have shown that as the temperature increases, the elastic modulus of the tape decreases, while the loss factor of the tape increases up to 20°C and then decreases to a constant level. The results from the three beams are in agreement, showing that the glass transition temperature of the tape is about 20°C, which implies viscoelastic properties at room temperature.